Investigating Students’ Online Learning Readiness (SOLR) in Developing Students’ Soft Skills: A Survey at English Education Study Program (EESP), Faculty of Teacher Training and Education (FKIP), Jambi University - Adrefiza Adrefiza (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Studies on Student Online Learning Readiness (SOLR) have been proliferating since the outbreak of the Covid-19 pandemic world-widely. The results seem to vary accordingly in terms of students’ levels, complexity, and contexts of its implementation across regions and countries. Through an internet survey questionnaire, involving 139 EESP students at the faculty of education, at Jambi University, this study investigates the levels of SOLR and how they contribute to the improvement of the students’ soft skills. Adapting Yu and Richardson’s (2015) model, the results show a relatively high SOLR level with an average score of (3.64) (out of the maximum 5.0) in three aspects (technical, social, and communication). Technical competencies were the highest level with an average score of (3.70) and Communication appear to be the lowest (3.59) in the evaluation. The study also proves that all aspects of SOLR contributed significantly to the improvement of the students’ soft skills (self-regulated, critical thinking, problem-solving, and time management) with an average score of (2.8) (out of 4.0). Despite the pessimistic claims in its implementation, the findings have displayed a reverse phenomenon, proving the fact that the student’s readiness at EESP along with its contribution to students’ soft skills far outweighs the expectation. Online learning, although, with several limitations, should be implemented wisely and thoroughly to obtain maximum results.